A Novel Lipopolysaccharide Recognition Mechanism Mediated by Internalization in Teleost Macrophages - Lu, Xin-Jiang; Ning, Ying-Jun; Liu, He; Nie, Li; Chen, Jiong (Frontiers in Immunology, 2018)
Macrophages in teleosts are less sensitive to lipopolysaccharide (LPS) compared to mammals. The functional equivalent of the mammalian LPS surface receptor in teleost macrophages for the pro-inflammatory response is either non-existent or replaced by negative regulation. LPS signaling in teleost macrophages remains unclear. Here, we found a scavenger receptor class B 2a (PaSRB2a) that played a crucial role in LPS signaling in teleost macrophages. The internalization of LPS and subsequent pro-inflammatory responses in macrophages were mediated by PaSRB2a, which is a novel isoform of the mammalian SRB2 gene. LPS internalization by PaSRB2a is dependent on its C-terminal intracellular domain. Following LPS internalization, it interacts with the ayu intracellular receptors nucleotide-binding oligomerization domain protein 1 (PaNOD1) and PaNOD2. Moreover, LPS pre-stimulation with sub-threshold concentrations reduced the effect of secondary LPS treatment on pro-inflammatory responses that were mediated by PaSRB2a. The pro-inflammatory responses in LPS-treated ayu were down-regulated upon PaSRB2a knockdown by lentivirus siRNA delivery. In grass carp and spotted green pufferfish, SRB2a also mediated LPS internalization and pro-inflammatory responses. Our work identifies a novel LPS signaling pathway in teleosts that differs from those in mammals, and contributes to the understanding of the evolution of pathogen recognition in vertebrates.